Komunikasi Interpersonal Ayah dan Anak Perempuan dalam Konteks Kesehatan Reproduksi - Chiara Fuadiyatul Athifah; Zainal Abidin Achmad (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study aims to understand the dynamics of interpersonal communication between fathers and daughters regarding reproductive health issues. This issue is important given the limited involvement of fathers in reproductive health education. The study employs a descriptive qualitative approach using a case study method, involving nine pairs of fathers and daughters (aged 14–18) who live in the same household. Data were collected through in-depth interviews to explore the experiences, strategies, and communication barriers that arise. The results indicate that interpersonal communication between fathers and daughters about reproductive health is often hindered by gender differences, societal taboos, and the dominant role of mothers. However, the use of open and empathy-based communication strategies proves effective in fostering openness. Daughters’ positive perceptions of their fathers’ involvement are influenced by the fathers’ supportive and nonjudgmental attitudes. These findings highlight the important role of fathers in reproductive health communication in shaping daughters’ comprehensive understanding and preparedness for puberty.